Hyperacusis and plasma levels of cytokines in migraine - Castro, Franciela Massi de; Silva, Aline Vitali da; Bello, Valéria Aparecida; Poli, Regina Célia (Headache Medicine, 2025)
IntroductionMigraine is a chronic pain that represents a public health problem and compromises quality of life, with an inflammatory factor involved in its pathophysiology.ObjectiveTo verify whether there is an increase in serum cytokines in patients with migraine associated with hyperacusis.MethodsThe sample consisted of 80 participants in the episodic and/or chronic migraine group, with/without aura, and 80 healthy individuals; aged 18 to 60 years of both sexes. Instruments used: ID-migraine, Migraine Disability Assessment (MIDAS); Short-Form Headache Impact Test (HIT-6), State Trait Anxiety Inventory (STAI) Y1 Y2, Beck Inventory, Allodynia and Hyperacusis Questionnaire; interleukin dosage by flow cytometry.ResultsThe sample was homogeneous for sex, age and race (p>0.05). There was an association between hyperacusis and migraine (p0.05) in migraine patients was observed.ConclusionIt was possible to verify that there was a significant difference in plasma cytokine levels between the groups. The increase in inflammatory markers indicates the possibility of complementary treatment, allowing the intervention of other professionals from multi and interdisciplinary teams.